Tebiras Sarong: A Number Theory Based Innovation Derived from the Menara Kudus Motif - Wahyuni, Fina Tri; Anggraini, Choirina Tri Wahyuni (Universitas Islam Negeri Sunan Kudus, 2025)
This study aims to develop and evaluate Sarung Tebiras, an innovative reinterpretation of the Menara Kudus sarong that integrates number theory concepts to cultivate students’ edupreneurial competencies. The research employed a 4D Research and Development (R&D) model consisting of the Define, Design, Develop, and Disseminate stages. Data were collected through expert validation forms, student response questionnaires, and edupreneurship assessments, and were analyzed using validation scoring, Likert-scale conversion, and feasibility testing. The development process produced a sarong design integrating number theory elements such as prime numbers, factorization, congruence, Euler’s theorem, and modulo arithmetic into the traditional Menara Kudus motif. Expert evaluations from material, design, and edupreneurship specialists indicated that the product met the criteria of “Very Worthy” and “Worthy”. Student responses indicated a positive reception, with an average score of 96%. The edupreneurship questionnaire yielded an average score of 39.21, categorized as “Very Good.” These results showed that Sarung Tebiras is feasible and effective as a culturally grounded innovative product that integrates mathematical concepts while enhancing students’ edupreneurial development. The novelty and contribution of this study lie in demonstrating how integrating number theory concepts into the Menara Kudus sarong motif can produce a contextual learning product that enhances mathematical understanding and stimulates students’ edupreneurial awareness. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi Sarung Tebiras, sebuah reinterpretasi inovatif dari sarung Menara Kudus yang mengintegrasikan konsep teori bilangan untuk menumbuhkan kompetensi edupreneurial siswa. Penelitian ini menggunakan model Penelitian dan Pengembangan (R&D) 4D yang terdiri dari tahap Define, Design, Develop, dan Disseminate. Data dikumpulkan melalui formulir validasi ahli, kuesioner respons siswa, dan penilaian edupreneurship, dan dianalisis menggunakan skor validasi, konversi skala Likert, dan uji kelayakan. Proses pengembangan menghasilkan desain sarung yang mengintegrasikan unsur-unsur teori bilangan seperti bilangan prima, faktorisasi, kongruensi, teorema Euler, dan aritmatika modulo ke dalam motif Menara Kudus tradisional. Evaluasi ahli dari spesialis material, desain, dan edupreneurship menunjukkan bahwa produk tersebut memenuhi kriteria